Experimental Investigation on the Characteristics of Pitch Motion for a Novel SPAR–type FOWT in Regular Waves - Fuad Mahfud Assidiq; Daeng Paroka; Habibi Palippui; Hidayatullah Hidayatullah; Muhammad Fajar Fitra Ramadan (Kapal: Jurnal Ilmu Pengetahuan dan Teknologi Kelautan, 2023)
Pitching mode is more crucial than heaving mode in assessing floating offshore wind turbine (FOWT) motion characteristics, especially the operation of the SPAR substructure. The aim of this paper is to develop an experimental method for improving the SPAR substructure to minimize unnecessary pitch motion. Toward this end, three vertical plate configurations based on the novel SPAR are being developed, known as the 3VP, 4VP, and 5VP models. In consideration of 0⁰, 30⁰, 60⁰, 90⁰-incidence, the pitch response characteristics of the proposed novel SPAR models are comprehensively evaluated in terms of submerged volume ratio, wave-induced motion, non-dimensional damping coefficient, and percentage of motion reduction. The model test results indicate that the 4VP model outperforms the other novel models with respect to dynamic response, particularly the incidence of 0⁰ and 90⁰. This study implies that the novel SPAR development is both feasible and effective in the modification of SPAR-type FOWT substructures.